Аспекти формування бізнес-середовища через призму інтеграційних процесів України і ЄС - Гавран, Володимир; Новаківський, Ігор (Видавництво «Редакція «УП», 2016)
The essence of information society incipience in Ukraine is revealed, the main characteristics of its development and differences from post-industrial society are defined. The above principles are confirmed by real examples of using information and communications technology in the business environment.
Keywords: інформаційне суспільство; бізнес-процеси; інформаційно- комунікаційні технології